Climate change and the size of glaciers in the Kuznetsky Alatau Mountains between 1975 and 2015 - M. M. Adamenko; Ya. M. Gutak; V. A. Antonova (Лëд и снег, 2017)
Climate change in the Kuznetsky Alatau (Western Siberia) highlands (on its eastern macroslope) was investigated using data of the Nenasthaya weather station collected for the last 40 years. It is the only highland station functioning now in the area under investigation. Basing on the correlation between average daily temperatures for the period 1974–1975, obtained at the Nenasthaya station and meteopost Karatash (located in front of the Kartash Glacier), we believe that the Nenasthaya one is enough representative for analysis of the climate in this glacio-nival zone. Linear trends for mean summer temperatures and annual precipitation sums had been calculated. Analysis of the linear trends has indicated that for the last 40 years the average summer temperature in the Kuznetsky Alatau increased by 1.3 °C with the growth rate of 0.33 °C/10 years. Average annual precipitation has also increased by 320 mm (the growth rate is 80 mm/10 years). These climatic changes did cause corresponding reactions of glaciers in the area. The analysis of current changes in the glacio-nival systems demonstrated that different morphological types of glaciers reacted to the current climate change in different ways. Small slope glaciers and perennial snowfields degraded significantly (70–90% of the area had melted) due to the temperature rise. Some ones transformed into the category of perennial snowfields.  Large corrie glaciers located on the leeward slopes of wide watersheds in the negative relief forms did only slight retreat. They mostly continue to exist because the amount of accumulated snow mass increased and, thus, compensated the ablation. The largest decrease in the area of glaciers took place in 2002–2004. Since 2005, large glaciers stopped to degrade and were in relative equilibrium with climate. This article presents estimation of dynamics of the Kuznetsky Alatau glaciers since their cataloging made in the 1980-s, and it contains the detailed information about fluctuation of areas of glaciers Karatash № 56, Cherno-Iyussky № 83, and Tsentralny № 87 in 1975–2015 received from data obtained in field measurements and remote sensing methods. The area increase of some individual glaciers since 2005 is shown. An effort to compare dynamics of main climatic factors having impact on the glaciations with the dynamics of the glacier areas had been made.